A ductility model for steel connections - Silva, L. Simões da (2001)
A model for the evaluation of the ductility of steel connections loaded in bending is presented in this paper. In the context of the component method, whereby a joint is modelled as an assembly of springs (components) and rigid links, using an elastic post-buckling analogy to the bi-linear elastic-plastic behaviour of each component, a general analytical model is proposed that yields the maximum rotation of the connection. Despite the complexity of the various connection types, the proposed model is able to provide analytical solutions for the moment-rotation response of a steel connection by using appropriate transformation criteria for assemblies of components in series and in parallel. The model is applied to typical beam-to-column connections, showing good agreement with numerical results.